Combination of Changes in CEA and CA199 Concentration After Neoadjuvant Chemoradiotherapy Could Predict the Prognosis of Stage II/III Rectal Cancer Patients Receiving Neoadjuvant Chemoradiotherapy Followed by Total Mesorectal Excision - Zhao J; Zhao H; Jia T; Yang S; Wang X (Cancer Management and Research, 2022)
Jieyi Zhao,1,2 Huamin Zhao,2 Tingting Jia,2 Shiru Yang,2 Xiaoyu Wang1,2 1Department of Neurosurgery, West China Hospital, Sichuan University, Chengdu, People’s Republic of China; 2West China Medical School, Sichuan University, Chengdu, People’s Republic of ChinaCorrespondence: Xiaoyu Wang, Tel +86 18980605160, Email yuxixi1052006@126.comBackground: Previous studies have shown that the levels of serum tumor markers CEA and CA19-9 were related to chemoradiotherapy. Therefore, it has been assumed that dynamic monitoring of these markers could predict the prognosis of stage II/III rectal cancer (RC). Therefore, this study proposed to evaluate the prognostic value of changes in serum tumor biomarkers for stage II/III RC patients undergoing neoadjuvant chemoradiotherapy (NCRT) followed by total mesorectal excision (TME).Methods: A total of 217 patients with stage II/III RC receiving NCRT followed by TME were retrospectively analyzed. Serum CEA and CA199 levels were measured within one week before NCRT and one week before TME. The optimal cut-off points of ∆CEA% and ∆CA199% for prognosis prediction were calculated by receiver operating characteristics (ROC) analysis. Independent prognostic predictors were identified by univariate and multivariate Cox regression analyses. To avoid the efficiency of ∆CEA% and ∆CA199% on serum tumor biomarker change (STBC) score, two models including and excluding ∆CEA% and ∆CA199% were established separately in multivariate analysis.Results: The optimal cut-off point for ∆CEA% and ∆CA199% were − 30.29% and 20.30%, respectively. Univariate analysis showed that ∆CEA%, ∆CA199%, STBC score, ypT staging and yN staging could predict OS. ypT staging and STBC score could predict DFS. In multivariate analysis, only ∆CA199% (HR = 0.468, 95% CI: 0.220– 0.994, p = 0.048), ypT staging (HR = 0.420, 95% CI: 0.182– 0.970, p = 0.042), and STBC score (HR = 0.204, 95% CI: 0.078– 0.532, p = 0.001) were independently related to OS; and STBC score (HR = 0.412, 95% CI: 0.216– 0.785, p=0.007) and ypT staging (HR = 0.421, 95% CI: 0.224– 0.792, p = 0.007) were independently related to DFS.Conclusion: We established a combined STBC score to predict the prognosis of stage II/III RC patients receiving NCRT followed by TME. The predictive value of the combined score was stronger than a single marker alone and even stronger than several pathological indicators.Graphical Abstract: Keywords: neoadjuvant chemoradiotherapy, stage II/III rectal cancer, total mesorectal excision, prognosis, STBC score